Environmental Impact Assessment of Pavements with the Addition of Recycled Post-consumer Polyethylene Terephthalate (RPET) through the Life Cycle Assessment (LCA) Methodology - Rivera Osorto, Mario René (2023)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Civil e Ambiental, 2023.